2016
DOI: 10.1016/j.scienta.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals the candidate genes associated with aroma metabolites and emission of pear (Pyrus ussuriensis cv.)

Abstract: Transcriptome profiling reveals the candidate genes associated with aroma metabolites and emission of pear (Pyrus ussuriensis cv.) ଝ a b s t r a c t Aroma is an important factor affecting pear fruit quality. However, the molecular basis for the development of aroma metabolites and their emission is poorly understood. Unripe 'Nanguoli' pear fruit has poor aroma, while the ripe fruit has an intense aroma, and calcium treatment can enhance the aroma, providing good material for transcriptome analysis.Digital gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…1). Consistent with these results of GO enrichment analysis, all biological categories except the biological process "death (GO: 0016265)" have been previously reported in a study conducted by Wei et al (2016) on aroma metabolites and emission of pear. Our results indicated that the biological process "death" might be related to aroma formation in rice in addition to other reported biological processes.…”
Section: Gene Ontology Enrichment Analysis Of the Differentially Exprsupporting
confidence: 88%
See 2 more Smart Citations
“…1). Consistent with these results of GO enrichment analysis, all biological categories except the biological process "death (GO: 0016265)" have been previously reported in a study conducted by Wei et al (2016) on aroma metabolites and emission of pear. Our results indicated that the biological process "death" might be related to aroma formation in rice in addition to other reported biological processes.…”
Section: Gene Ontology Enrichment Analysis Of the Differentially Exprsupporting
confidence: 88%
“…The enrichment analysis of cellular component revealed that three categories were enriched by differentially expressed genes. In accordance with these results of GO enrichment analysis, all cellular component categories including membrane-enclosed lumen (GO : 0031974), macromolecular complex (GO : 0032991), and organelle part (GO : 00044422) have been previously reported in a study by Wei et al (2016).…”
Section: Gene Ontology Enrichment Analysis Of the Differentially Exprsupporting
confidence: 85%
See 1 more Smart Citation
“…Fruit maturation is a complex physiological process, which is accompanied by a series of biochemical processes such as sugar accumulation (Zhang Y.J. et al, 2014;Xu et al, 2020), acid reduction (Jiang et al, 2020), aroma production (Wei et al, 2016), pigment accumulation (Gan et al, 2019), flavonoid metabolism (Huang et al, 2020), and endogenous hormone change (Wang et al, 2016). The difference of fruit quality between early mature and late mature cultivar in our study was mainly reflected in the SSC, DM, and pigment contents.…”
Section: Discussion Low Concentration Of Endogenous Hormones Promote Starch Hydrolyzed To Sugarsmentioning
confidence: 52%
“…Regarding Pyrus ussuriensis Maxim aroma evaluation, some scholars have evaluated the types, quantity, and volatile content of the aroma in Pyrus ussuriensis Maxim, including Nanguoli, Huaguai, and Jianbali [ 13 , 20 , 21 ], mainly using headspace solid-phase microextraction (HS-SPME) in combination with gas chromatography-mass spectrometry (GC-MS) technology. Some researchers have also studied the physiological mechanism of aroma formation and release in “Nanguoli” fruit and identified relevant candidate genes via calcium regulation, providing valuable data for further research into the molecular mechanism of pear fruit aroma regulation [ 19 ]. However, the number of aroma components reported in Pyrus ussuriensis Maxim is still limited, and the analysis of aroma characteristics has not been adequately reported.…”
Section: Introductionmentioning
confidence: 99%